2008
DOI: 10.1590/s0103-84782008000100046
|View full text |Cite
|
Sign up to set email alerts
|

Características químicas e valores energéticos de farelos de soja do oeste e sudoeste do Paraná

Abstract: RESUMO Foi realizado um estudo para determinar a variabilidade de características químicas e valores energéticos de farelos de soja (FS) do oeste e sudoeste do Paraná. Foram estudadas 40 amostras colhidas em 10 processadores e distribuidores durante quatro meses consecutivos. Houve diferenças (P<0,05) entre os teores de matéria seca (MS) dos farelos de soja (FS) analisados. O FS 10 apresentou menor (P<0,05) teor de MS (86,72%) em relação aos FS 2, 4, 5, 6 e 9 (88,96, 90,60, 89,19, 89,08 e 88,72%, respectivame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…The chemical composition of soybean meal had only the contents of CP and MM changing depending on the seasons (Table 3). Despite variations, the obtained values are similar to those found by Rieger et al (2008), who studied the composition of soybean meals of the West and Southwest regions of Paraná, and Zambom et al (2001), who studied the nutritional value of feed for ruminants in the North West of Paraná. The CP, however, showed variations depending on the seasons, but these variations are not due specifically to climatic conditions, but rather to the origin of the grains used for bran production (Grieshop et al, 2003) and the shell proportion added to the bran (Zambom et al, 2001).…”
Section: Resultssupporting
confidence: 84%
“…The chemical composition of soybean meal had only the contents of CP and MM changing depending on the seasons (Table 3). Despite variations, the obtained values are similar to those found by Rieger et al (2008), who studied the composition of soybean meals of the West and Southwest regions of Paraná, and Zambom et al (2001), who studied the nutritional value of feed for ruminants in the North West of Paraná. The CP, however, showed variations depending on the seasons, but these variations are not due specifically to climatic conditions, but rather to the origin of the grains used for bran production (Grieshop et al, 2003) and the shell proportion added to the bran (Zambom et al, 2001).…”
Section: Resultssupporting
confidence: 84%
“…Regarding the NDF, ADF and CF, variation was also observed between the SBM studied and, according to Rieger et al (2008), NDF is an estimate of the amount of carbohydrates of low digestibility to non-ruminants, including soybean hull and nonstarch polysaccharides. The fiber content of SBM is influenced by adding lower or higher amounts of soybean hulls, as well as the amount of CP.…”
Section: Resultsmentioning
confidence: 98%
“…However, a greater variation was seen in the values of ether extract and fibrous fractions. The variability found for the level of ether extract in the soybean meal is due to the efficiency of the oilextraction process (OST et al, 2005;RIEGER et al, 2008), and may contribute to the variation found in the values of digestible and metabolizable energy. DE: digestible energy (kcal/kg); ME: metabolizable energy (kcal/kg); CP: crude protein (%); EE: ether extract (%); CP: crude fiber (%); ADF acid detergent fiber (%); NDF: neutral detergent fiber (%); MM: mineral matter (%); *significant at 5% probability by t-test (P<0,05); ** significant at 1% probability by t-test (P<0,01)…”
Section: Resultsmentioning
confidence: 99%